2017
DOI: 10.5455/jice.20161229055245
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for homeopathy in breast cancer surgery? A first randomized clinical trial on treatment with Arnica montana to reduce postoperative seroma and bleeding in patients undergoing total mastectomy

Abstract: Aim:This study aimed to evaluate the benefits of Arnica montana on post-operative blood loss and seroma production in women undergoing unilateral total mastectomy by administering Arnica Montana 1000 Korsakovian dilution (1000 K).Materials and Methods:From 2012 to 2014, 53 women were randomly assigned to A. montana or placebo and were followed up for 5 days. The main end point was the reduction in blood and serum volumes collected in drainages. Secondary end points were duration of drainage, a self-evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 32 publications
0
31
0
2
Order By: Relevance
“…13 In another, coherent domains are formed "among the molecules of the water-alcohol solvent, as predicted by quantum electrodynamics." 14,15 The nanodose levels that persist in homeopathic medicines are comparable to the levels at which the body's hormones and cell-signaling agents operate. These two qualities of homeopathy-the active ingredient being present only in nanoparticles and the mechanism of action based on conveying information rather than its medicinal substance-give homeopathic medicines their unique qualities: the patient needs less and less of them over time; they do not create dependency or withdrawal; they do not interact with other medications; and they can heal other health conditions at the same time in addition to the chief complaint, that is, they provide side benefits instead of side effects.…”
Section: Advantages Of Homeopathymentioning
confidence: 99%
“…13 In another, coherent domains are formed "among the molecules of the water-alcohol solvent, as predicted by quantum electrodynamics." 14,15 The nanodose levels that persist in homeopathic medicines are comparable to the levels at which the body's hormones and cell-signaling agents operate. These two qualities of homeopathy-the active ingredient being present only in nanoparticles and the mechanism of action based on conveying information rather than its medicinal substance-give homeopathic medicines their unique qualities: the patient needs less and less of them over time; they do not create dependency or withdrawal; they do not interact with other medications; and they can heal other health conditions at the same time in addition to the chief complaint, that is, they provide side benefits instead of side effects.…”
Section: Advantages Of Homeopathymentioning
confidence: 99%
“…In a recent paper, Sorrentino et al., reported that a homeopathic preparation of an extract from Arnica montana L, known as Arnica 1000 K, significantly reduced the amount of post-operative blood and seroma (improving bleeding) in female subjects who underwent an unilateral total mastectomy. 1 This double blind randomized controlled trial versus placebo was performed throughout two years-long period, from 2012 to 2014, and about 53 patients (26 cases and 27 controls) with an age range 20–75 years and hospitalized for unilateral total mastectomy, were enrolled. 1 In their study, the authors stated that patients underwent also a standardized protocol of treatment for surgical procedures including an antithrombotic prophylaxis with 4000 UI heparin 12 h before surgery.…”
mentioning
confidence: 99%
“… 1 This double blind randomized controlled trial versus placebo was performed throughout two years-long period, from 2012 to 2014, and about 53 patients (26 cases and 27 controls) with an age range 20–75 years and hospitalized for unilateral total mastectomy, were enrolled. 1 In their study, the authors stated that patients underwent also a standardized protocol of treatment for surgical procedures including an antithrombotic prophylaxis with 4000 UI heparin 12 h before surgery. 1 Patients who followed a randomization blinded protocol received a 30% v/v ethanol preparation of Arnica 1000 K (five drops sublingual) or a placebo (i.e.…”
mentioning
confidence: 99%
See 2 more Smart Citations